Population ecology of Heteromys pictus (Rodentia: Heteromyidae), in a tropical deciduous forest with human disturbance, in Oaxaca coast, Mexico - Briones-Salas, Miguel (2016)
Spiny pocket mice Liomys and Heteromys are forest-dwelling granivorous rodents distributed in seasonally dry forest or thorn scrub along the Pacific lowlands or xeric regions in the Mexican Plateau. We analyzed the population dynamics of the spiny pocket mouse Heteromys pictus, in the coast of Oaxaca, Mexico, in two sites of tropical deciduous forest with different degrees of disturbance: ZPP = less disturbed site, and ZMP = more disturbed site. Two plots were established in each area with 66 trap stations; we used the capture-recapture method and trapping for 12 periods for one year. Population density was estimated using the method of Minimum Number of Individuals Known Alive (MNKA). We captured 706 individuals, 290 for the ZPP and 416 for the ZMP. The population density ranged from 28 to 142 ind./ha for both zones, but it was higher for the ZMP (54 against 142 ind./ha). The population density for both areas increased during the rainy season and coincided with the increased recruitment of adults. Reproductive activity occurred throughout the study period in both areas, but it was higher for the ZMP. The sex ratio in the ZPP was 1:1 while in the ZMP was 1:0.75. In the ZMP we found a higher population density and reproductive activity in females, compared to the ZPP. These results suggest that H. pictus prefers the ZMP, indicating that thespeciesisnot significantly affected by human disturbance in the studied location.